NADH‐dependent glutamate synthase plays a crucial role in assimilating ammonium in the Arabidopsis root. Issue 1 (2nd April 2014) - Konishi, Noriyuki; Ishiyama, Keiki; Matsuoka, Kaya; Maru, Ikumi; Hayakawa, Toshihiko; Yamaya, Tomoyuki; Kojima, Soichi
<x xml:space="preserve">Abstract</x> Plant roots under nitrogen deficient conditions with access to both ammonium and nitrate ions, will take up ammonium first. This preference for ammonium rather than nitrate emphasizes the importance of ammonium assimilation machinery in roots. Glutamine synthetase (GS) and glutamate synthase (GOGAT) catalyze the conversion of ammonium and 2‐oxoglutarate to glutamine and glutamate. Higher plants have two GOGAT species, ferredoxin‐dependent glutamate synthase (Fd‐GOGAT) and nicotinamide adenine dinucleotide (NADH)‐GOGAT. While Fd‐GOGAT participates in the assimilation of ammonium, which is derived from photorespiration in leaves, NADH‐GOGAT is highly expressed in roots and its importance needs to be elucidated. While ammonium as a minor nitrogen form in most soils is directly taken up, nitrate as the major nitrogen source needs to be converted to ammonium prior to uptake. The aim of this study was to investigate and quantify the contribution of NADH‐GOGAT to the ammonium assimilation in Arabidopsis (Arabidopsis thaliana Columbia) roots. Quantitative real‐time polymerase chain reaction (PCR) and protein gel blot analysis showed an accumulation of NADH‐GOGAT in response to ammonium supplied to the roots. In addition the localization of NADH‐GOGAT and Fd‐GOGAT did not fully overlap. Promoter–β‐glucuronidase (GUS) fusion analysis and immunohistochemistry showed that NADH‐GOGAT was highly accumulated in non‐green tissue like vascular bundles, shoot apical meristem, pollen, stigma and roots. Reverse genetic approaches suggested a reduction in glutamate production and biomass accumulation in NADH‐GOGAT transfer DNA (T‐DNA) insertion lines under normal CO2 condition. The data emphasize the importance of NADH‐GOGAT in the ammonium assimilation in Arabidopsis roots.